In search of the next super models - Alexander Goedel; Niels Grote Beverborg; Makoto Sahara; Kenneth R Chien (EMBO Molecular Medicine)
Abstract The advent of pluripotent stem cell biology and facile genetic manipulation via CRISPR technology has ushered in a new era of human disease models for drug discovery and development. While these precision “super models” hold great promise for tailoring personalized therapy, their full potential and in vivo validation have remained elusive.